Implementasi Manajemen Keuangan Syariah Sebagai Salah Satu Upaya Untuk Memajukan dan Mengembangkan UMKM di Indonesia - Afief Mubayyin; Wahyudin Abdullah (Universitas Islam Lamongan, 2021)
Abstract: SME is one of the pillars of the Indonesian economy. Data in 2020 shows that the number of SME in Indonesia has reached 64.2 million business units. However, it does not mean that MSME in Indonesia is far from all the problems. One of the problems experienced by SME is that many business entrepreneurs do not understand how to manage the finances and assets they get. Hence, many SME in Indonesia have gone bankrupt. This study uses qualitative methods. The data are obtained from existing scientific journals, and provided by related parties, as well as books that discuss financial management and SME. The results obtained from this study are about how SME practices simple and easy-to-understand accounting activities and applies Islamic values. On the other hand, this study explains the way SME subjects invest with limited capital and also how to get capital that is far from riba (interest). Keywords: SME; financial management; Islamic financial management